Modalidade consultoria - Disal Consórcio - BORGES, Amanda Luiz Rodrigues; CARVALHO, Lavinnya Rodrigues de; FIGUEIREDO, Joice Aparecida Silva; SANTOS, Micheli Martins dos (238, 2022)
O presente trabalho irá abordar o impacto de um treinamento mal estruturado e suas falhas no dia a dia. Em uma breve entrevista com uma colaboradora, foi possível identificar os pontos a melhoria nesse treinamento. No decorrer do trabalho, mostraremos propostas sobre a elaboração de um treinamento eficaz com um conteúdo de fácil aprendizado. Serão apresentadas alternativas para melhoria no treinamento inicial deste colaborador e quais serão os resultados caso as melhorias sejam implementadas.

This paper will address the impact of poorly structured training and its failures on a daily life. In a brief interview with a collaborator, it was possible to identify the points to improvement in this training. In the course of the work, we will show proposals on the elaboration of effective training with an easy-to-learn content. Alternatives will be presented for improvement in the initial training of this employee and what the results will be if the improvements are implemented. In the course of the work we will give suggestions for effective training with an easy-to-learn content. Alternatives will be presented for improvement in the initial training of this employee and what the results will be if the improvements are implemented.
Consultancy modality - Disal Consortium
Keywords: Consultoria de empresas; Treinamento de pessoal; Gestão e Negócios